Biology and ecology of largemouth bass Micropterus salmoides in two temperate South African impoundments - Taylor, Geraldine Claire (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
Globally largemouth bass Micropterus salmoides is one of the most widely introduced game fish species which has now become invasive in many countries. Well researched in its native North America, there are few studies on this species in its introduced range. This study aims to improve the understanding of the biology and ecology of M. salmoides in temperate southern Africa, where it threatens native biota and supports a popular recreational fishery. This aim was addressed by assessing the age, growth, maturity, reproductive seasonality, feeding, mortality and movement, of two M. salmoides populations from Wriggleswade (1000 ha, 723 m amsl, 32Âº35'S; 27Âº33'E) and Mankazana (35 ha, 66 m amsl, 33Âº09'S; 26Âº57'E) Dams in the Eastern Cape of South Africa. The most suitable structure for ageing M. salmoides was determined by comparing the accuracy and precision of otoliths and scales. Scales tended to underestimate the age of fish older than five years. Sectioned sagittal otoliths were the more precise structures for ageing (otoliths CV = 15.8 vs. scales CV = 21.9). The periodicity of growth zone formation was validated as annual for otoliths using both edge analysis (EA), and mark recapture of chemically tagged fish (MRCT). EA indicated one annual peak in the frequency of opaque margins between September and January using a periodic logistic regression and a binomial model linked with a von Mises distribution for circular data. MRCT showed the linear relationship between time at liberty and number of growth zones distal to the fluorescent band was not significantly different from one (slope = 0.89). Reproduction was similar to that in native and non-native populations with fish reaching age at 50% maturity at ca. two years, and length at 50% maturity at 259-290 mm FL depending on growth rate. Spawning season occurred in the spring months of August to October. The Wriggleswade Dam population reached similar ages (14 yrs) to populations in temperate North America. Growth was described using the von Bertalanffy growth equations of (Lt = 420(1-áµ‰â »Â°Â·Â³Â³â ½áµ—â ºÂ°Â·Â²Â¹â ¾) mm FL in Wriggleswade and (Lt = 641(1-áµ‰â »Â°Â·Â²Â²â ½áµ—â ºÂ°Â·â ·â ¶â ¾) mm FL in Mankazana. Growth performance of both populations, described using the phi prime index, seemed to be correlated with temperature and the Wriggleswade Dam population (Î¦' = 2.8) grew similarly to those native temperate North American populations and the non-native populations of Japan and Italy. The Mankazana population had a higher growth performance (Î¦' = 2.9) compared to Wriggleswade and growth was comparable to other nonnative African populations. Both populations utilised all available food resources, with the Mankazana population being in better condition than the Wriggleswade population as a result of a more diverse diet, highly abundant food sources throughout the year, and potentially the adoption of a more conservative ambush feeding strategy. The Wriggleswade population, which was utilised by competitive anglers, showed low mortality rates (Z = 0.43 yrâ »Â¹), and translocated fish dispersed from the common release site, travelling an average distance of 4km over the study time of 494 days. These results indicated that M. salmoides are successful in these environments, growing at expected temperature dependant rates, maturing at two years, using all available food groups, and suffering from low mortality. It is therefore likely that they will persist in South Africa and establish where introduced.
Keywords: Largemouth bass -- Ecology -- South Africa -- Eastern Cape; Largemouth bass -- Behavior -- South Africa -- Eastern Cape; Largemouth bass -- Growth -- South Africa -- Eastern Cape; Largemouth bass -- Reproduction -- South Africa -- Eastern Cape; Largemouth bass -- Food -- South Africa -- Eastern Cape; Largemouth bass -- Age determination -- South Africa -- Eastern Cape; Introduced fishes -- South Africa -- Eastern Cape; Fish populations -- South Africa -- Eastern Cape; Otoliths; Largemouth bass -- South Africa -- Eastern Cape